2004
DOI: 10.1016/j.ehj.2004.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and haemodynamic effects of sildenafil in pulmonary hypertension: acute and mid-term effects

Abstract: Sildenafil is well tolerated in its intravenous and oral forms and appears to improve both pulmonary haemodynamics and the clinical status of patients with pulmonary hypertension after 3 months of oral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 25 publications
6
58
0
3
Order By: Relevance
“…Erectile dysfunction (ED) is a common medical condition linked both to endothelial dysfunction [1][2][3][4][5][6][7][8][9][10][11][12][13] as well as multiple other comorbid conditions. [14][15][16][17] Historically, the treatment for ED has been limited to a selected group of specialists, namely urologists and sexual therapists.…”
Section: Introductionmentioning
confidence: 99%
“…Erectile dysfunction (ED) is a common medical condition linked both to endothelial dysfunction [1][2][3][4][5][6][7][8][9][10][11][12][13] as well as multiple other comorbid conditions. [14][15][16][17] Historically, the treatment for ED has been limited to a selected group of specialists, namely urologists and sexual therapists.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In adults with PH, sildenafil has improved survival rates, exhibited low toxicity, and is available as an enteral preparation that is more practical for long-term, outpatient therapy. [13][14][15][16][17][18][19][20] Early clinical experience indicates that sildenafil treatment may be efficacious for infants with BPD-PH, with evidence suggesting that sildenafil normalizes lung development and may improve outcomes. [21][22][23][24][25] However, practice patterns for sildenafil treatment in infants with BPD-PH have not been fully reported; these patterns include variables associated with exposure, timing of initiation, length of treatment, and interhospital variation in use.…”
mentioning
confidence: 99%
“…6,7) Pulmonary vasodilator therapy improves outcomes in patients with idiopathic PAH, and has also been reported to be effective in patients with other types of PAH. [8][9][10][11][12][13] This therapy may reduce pulmonary vascular resistance (Rp) in patients who were previously thought to have irreversible pulmonary vascular disease.…”
Section: R Ecent Advances In Pediatric Cardiac Surgery Techniquesmentioning
confidence: 99%
“…6,42) These vasodilators have been shown to improve functional status and survival in patients with idiopathic PAH. [6][7][8][9][10][11][12][13] Pulmonary vasodilator therapy is now being used to treat PAH in patients with CHD, including those with Eisenmenger syndrome. Many reports have indicated that the endothelin receptor antagonist bosentan is effective for improving clinical outcomes and exercise capacity in patients with Eisenmenger syndrome.…”
Section: How Does Pulmonary Vasodilator Therapy Affect Outcomes In Pamentioning
confidence: 99%
See 1 more Smart Citation